2020
DOI: 10.1016/j.marenvres.2019.104851
|View full text |Cite
|
Sign up to set email alerts
|

Fish assemblages cope with ocean acidification in a shallow volcanic CO2 vent benefiting from an adjacent recovery area

Abstract: Shallow CO 2 vents are used to test ecological hypotheses about the effects of ocean acidification (OA). Here, we studied fish assemblages associated with Cymodocea nodosa meadows exposed to high pCO 2 /low pH conditions at a natural CO 2 vent in the Mediterranean Sea. Using underwater visual census, we assessed fish community structure and biodiversity in a low pH site (close to the CO 2 vent), a close control site and a far control site, hypothesising a decline in biodiversity and a homogenization of fish as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 59 publications
1
16
0
Order By: Relevance
“…Overall, by showing that OA will decrease parental care and guarding activity in the S. ocellatus nesting male, this study may contribute to emphasize the behaviour as a first strategy by which this widespread Mediterranean wrasse responds to environmental change. The present findings along with previous research assessing the mating behaviour, the reproductive success, and the abundance of the Mediterranean ocellated wrasse along a CO2 gradientsuggest this species may maintain fitness and population persistence under OA conditions (Milazzo et al, 2016;Cattano et al, 2016;Mirasole et al, 2020). Future research efforts should also consider the fundamental link between species behaviour and population responses under changing environmental conditions, for instance deepening the different processes and mechanisms underpinning tolerance to elevated CO2 in marine populations, including transgenerational effects (Schunter et al, 2016;Tsang et al, 2020;Petit-Mart et al, 2021).…”
Section: Discussionsupporting
confidence: 60%
“…Overall, by showing that OA will decrease parental care and guarding activity in the S. ocellatus nesting male, this study may contribute to emphasize the behaviour as a first strategy by which this widespread Mediterranean wrasse responds to environmental change. The present findings along with previous research assessing the mating behaviour, the reproductive success, and the abundance of the Mediterranean ocellated wrasse along a CO2 gradientsuggest this species may maintain fitness and population persistence under OA conditions (Milazzo et al, 2016;Cattano et al, 2016;Mirasole et al, 2020). Future research efforts should also consider the fundamental link between species behaviour and population responses under changing environmental conditions, for instance deepening the different processes and mechanisms underpinning tolerance to elevated CO2 in marine populations, including transgenerational effects (Schunter et al, 2016;Tsang et al, 2020;Petit-Mart et al, 2021).…”
Section: Discussionsupporting
confidence: 60%
“…This pattern can be linked to the greater vulnerability of the seagrass under acidified conditions, due to the biological erosion performed by Sarpa salpa (Linnaeus, 1758) through grazing [13,58]. In fact, rcent studies reported a higher abundance of the herbivorous fish S. salpa in the vents area if compared to adjacent ambient pH stations [63,64]. Posidonia oceanica leaves seem more palatable under acidified conditions, due to their nutritional quality [65][66][67] and the reduction or disappearance of calcareous epiphytes [13].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, studies have reported heritability of behavioural response to high CO 2 (Welch & Munday, 2017) and intergenerational acclimation of species to elevated CO 2 (Allan et al, 2014; Munday, 2014; Schunter et al, 2016, 2018; Stiasny et al, 2018; Strader et al, 2020; Tsang et al, 2020) which could potentially result in adaptation to ocean acidification over multiple generations. Additionally, other environmental factors such as nutrient gradients, species composition, habitat modifications, and predation risk can interact with CO 2 to affect species responses to OA (Mirasole et al, 2019; Munday et al, 2014; Nagelkerken et al, 2015; Zunino et al, 2019). Volcanic CO 2 seeps in the ocean, where emission of CO 2 -rich fluids locally reduce pH, can be used as natural analogues to study the effects of long-term exposure of fish to elevated CO 2 in their natural environment.…”
Section: Introductionmentioning
confidence: 99%
“…Increased primary productivity at CO 2 seeps for instance may help certain fish species to meet the increased energy demands of living in a high CO 2 environment (Connell et al, 2013). Shifts in habitat forming species, trophic diversity and fish assemblages at CO 2 seeps have been reported which could obscure some of the negative effects of OA on fish behaviour (Fabricius et al, 2011; Hall-Spencer et al, 2008; Mirasole et al, 2019; Nagelkerken et al, 2015; Vizzini et al, 2017). For example, gobies from the CO 2 seeps in Vulcano Island, Italy living in more open habitats showed reduced predator escape behaviour, however, the same was not observed in gobies living in more sheltered sites indicating the influence of habitat on species response to OA (Nagelkerken et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation